High-temperature daub and preparation method thereof
By using lightweight mullite brick powder, alumina powder, silicon carbide powder and other raw materials in high-temperature slurry, and performing particle grading and modification treatment, the problem of existing high-temperature slurry expansion and fire swelling at high temperatures is solved. It significantly improves adhesion and thermal shock resistance, reducing energy waste.
Patent Information
- Application Number
- CN202411702852.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-26
AI Technical Summary
The existing high-temperature mud expands heat at a lower temperature. After the temperature rises, the liquid phase appears and shrinks, which is prone to fire, has poor adhesion and corrosion resistance, is difficult to construct and operate, and has a high thermal conductivity, resulting in waste of energy.
Lightweight mullite brick powder, alumina powder, and silicon carbide powder are used as raw materials, and the use of particle grading and hydroxypropyl cellulose modified bentonite can improve the bonding and thermal shock resistance, and add dispersants, Water reducing agent and anti-carburizing agent to improve fluidity and carbon permeability.
It significantly improves the adhesion, thermal shock resistance and thermal insulation of high-temperature mud, reduces the thermal expansion coefficient and thermal conductivity, enhances the stability of the furnace structure, and reduces safety accidents and energy waste.
Smart Images

Figure BDA0005153782720000081 
Figure BDA0005153782720000082 
Figure BDA0005153782720000192
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of mortar, in particular to high-temperature mortar and a preparation method thereof. Background Art
[0002] High temperature mortar is an indispensable bonding material for building kiln walls, kiln passages, flues and fireboxes. It helps stabilize the structure of the furnace and plays a key role in reducing heat dissipation, which can greatly reduce the cost of building kilns. High temperature mortar and refractory masonry bear the same load and high temperature, and its quality directly affects the life of refractory masonry. Existing high temperature mortar has the following defects: (1) High temperature mortar expands when heated at a relatively low temperature. When the temperature rises to a certain level, a liquid phase appears and it begins to shrink, which is easy to cause fire. Not only does the energy-saving effect fail to meet the requirements, the furnace wall structure is unstable, and safety accidents occur; (2) There are defects such as poor adhesion and corrosion resistance, and it is easy to corrode; (3) The construction operation is difficult. If the high temperature mortar is too thin, it is easy to flow from the brick joints. If the high temperature mortar is too dry, the fluidity is poor, which affects the construction efficiency and its bonding performance will also deteriorate; (4) The high temperature mortar has a high thermal conductivity coefficient, and a large amount of heat energy is transmitted to the outside through the gaps, causing energy waste, increasing production costs, and product quality cannot be guaranteed.
[0003] In view of the existing defects, the present invention will prepare a new type of high-temperature mortar, which has important value. Summary of the invention
[0004] The object of the present invention is to provide a high temperature mortar and a preparation method thereof to solve the problems raised in the prior art.
[0005] To achieve the above object, the present invention provides the following technical solutions:
[0006] A high-temperature mortar comprises the following components in mass fractions: 70-75% mortar powder, 24-27% binder, and 1-3% additive;
[0007] The cement powder comprises the following components in parts by weight: 25-40 parts of graded lightweight mullite brick powder, 15-30 parts of graded alumina powder, 8-10 parts of graded silicon carbide powder, 15-25 parts of Suzhou mud, 10-20 parts of Guangdong mud, and 1.46-6.25 parts of hydroxypropyl cellulose modified bentonite;
[0008] The binder is obtained by mixing silica sol, aluminum dihydrogen phosphate, polyvinyl alcohol modified ceramic fiber and deionized water in a mass ratio of 2: (0.5-1): (0.2-0.4): 2;
[0009] The additive is obtained by mixing a dispersant, a water reducing agent and an anti-carburizing agent in a mass ratio of 1:3:2.
[0010] Furthermore, the specific gradation ratio of the graded lightweight mullite brick powder is: 75-80% of lightweight mullite brick powder with a particle size of less than 0.074 mm, and 20-25% of lightweight mullite brick powder with a particle size of 0.074-1 mm.
[0011] Furthermore, the specific gradation ratio of the graded alumina powder is: 75-80% of the alumina powder with a particle size of less than 0.074 mm, and 20-25% of the alumina powder with a particle size of 0.074-1 mm.
[0012] Furthermore, the specific gradation ratio of the graded silicon carbide powder is: 75-80% of silicon carbide powder with a particle size of less than 0.074 mm, and 20-25% of silicon carbide powder with a particle size of 0.074-1 mm.
[0013] In the present invention, by simultaneously introducing light mullite brick powder, alumina powder, and silicon carbide powder as raw materials of high temperature mortar, the chemical composition thereof is equivalent to the chemical composition of refractory masonry, the prepared high temperature mortar has stronger bonding property, and can also greatly avoid harmful chemical reactions of different materials, causing erosion of high temperature mortar. Among them, the thermal conductivity of light mullite brick powder is low, so it can be used as a heat-insulating material to improve the heat insulation of high temperature mortar and play a role in reducing heat loss; although silicon carbide has a high thermal conductivity, its thermal expansion coefficient is low, so a small amount of silicon carbide is added in the present invention, which can reduce the thermal expansion coefficient of high temperature mortar and enhance its thermal shock resistance. In addition, the synergy of light mullite brick powder, alumina powder, and silicon carbide powder can also improve the flexural strength of high temperature mortar, ensure that under high temperature environment, high temperature mortar still has a high bonding strength, and the integrity of high temperature mortar is good, and the load borne is more uniform, which can greatly enhance the stability of furnace structure and reduce safety accidents. Furthermore, in the present invention, the particle grading of the three is set to achieve the purpose of controlling the bonding time and shrinkage rate of the high-temperature mortar, while achieving faster hardening and maintaining higher performance.
[0014] Furthermore, the particle size of the Suzhou mud and Guangdong mud is 3 to 5 μm.
[0015] Furthermore, the preparation method of the hydroxypropyl cellulose modified bentonite is: grind the bentonite through a 1 mm sieve, then slowly add it to the hydroxypropyl cellulose solution, stir and mix at a speed of 30 to 50 r / min for 5 to 10 hours, filter, dry, grind, and pass through a 1 mm sieve to obtain hydroxypropyl cellulose modified bentonite.
[0016] Furthermore, the bentonite is any one of sodium-based bentonite or calcium-based bentonite.
[0017] Furthermore, the mass ratio of the bentonite to the hydroxypropyl cellulose is 1:(0.02-0.05).
[0018] The present invention is designed to modify the bentonite added to the cement powder. Since bentonite has excellent stability, it can form a tiny network void structure in the high-temperature cement during the mixing process of the cement powder and the binder and additive, and then after the high-temperature cement is cured, the expansion effect caused by heat can be alleviated, and the crack resistance of the high-temperature cement can be improved. In addition, bentonite also has: (1) good water retention, which can improve the fluidity and plasticity and enhance the workability of the high-temperature cement; (2) good bonding force, which enhances the bonding strength of the high-temperature cement before and after curing. In order to enhance the role of bentonite in high-temperature cement, further, hydroxypropyl cellulose is used in the present invention to modify it to obtain hydroxypropyl cellulose modified bentonite. Hydroxypropyl cellulose has the effects of water reduction, bonding and dispersion, so the dispersion performance of the prepared hydroxypropyl cellulose modified bentonite will be enhanced, which is more conducive to its uniform formation of a tiny network void structure in the high-temperature cement, and at the same time, its fluidity and bonding properties will be enhanced, greatly enhancing the overall performance of the high-temperature cement. However, the amount of bentonite added should not be too much, as too much will cause the high-temperature mortar to be too sticky and cause a significant decrease in the fluidity of the high-temperature mortar. Therefore, it is advisable to control the amount added to about 2-5% of the total amount of other mortar powders.
[0019] Furthermore, the preparation method of the polyvinyl alcohol modified ceramic fiber is as follows: (1) adding vinyl triethoxysilane, deionized water and anhydrous ethanol in a mass ratio of 1:1:10 into a reaction container, stirring and mixing, and adding acetic acid to adjust the pH to 4.5-5.5, and continuing to stir and mix for 5-15 minutes to obtain a silane hydrolyzate; (2) dispersing the ceramic fiber in n-butanol to obtain a 5wt% ceramic fiber dispersion; (3) heating the ceramic fiber dispersion to 70-90°C, and slowly adding the silane hydrolyzate dropwise, and dripping After the addition is completed, stirring is continued for 2 to 8 hours, and vinyl ceramic fibers are obtained by filtering, washing, and drying; (4) polyvinyl alcohol and thioglycolic acid are added to a 4 to 6 wt % sulfuric acid solution, and the mixture is stirred and reacted at 70 to 90° C. for 1 to 4 hours, and purified by dialysis to obtain thiolated polyvinyl alcohol; (5) thiolated polyvinyl alcohol, vinyl ceramic fibers, and a photoinitiator are added to anhydrous ethanol, and ultrasonically dispersed for 5 to 15 minutes, and reacted by ultraviolet irradiation for 15 to 45 minutes, and separated, washed, and dried to obtain polyvinyl alcohol-modified ceramic fibers.
[0020] Furthermore, the mass ratio of the vinyltriethoxysilane to the ceramic fiber is (0.04-0.06):1.
[0021] Furthermore, the mass ratio of the polyvinyl alcohol to thioglycolic acid is 1:(0.8-1).
[0022] Furthermore, the mass ratio of the mercaptolated polyvinyl alcohol, the vinylated ceramic fiber and the photoinitiator is 1:(0.3-0.5):(0.01-0.03).
[0023] Furthermore, the ceramic fibers include but are not limited to a combination of one or more of zirconium oxide fibers, silicon carbide fibers, silicon nitride fibers, aluminum silicate fibers, and mullite fibers.
[0024] In the embodiment of the present invention, the ceramic fiber is preferably zirconia fiber.
[0025] Ceramic fiber has excellent characteristics such as low thermal conductivity, low thermal expansion coefficient, high strength, and good processing performance. Therefore, the present invention is designed to introduce it into high-temperature mortar to improve the relevant thermal properties of high-temperature mortar. At the same time, after the high-temperature mortar is cured, it can also act on the high-temperature mortar as a "skeleton-type" binder, effectively preventing its cracking defects caused by high temperature, and further improving the thermal shock resistance of the high-temperature mortar. Considering that ceramic fiber has a tendency to agglomerate, it is directly used to be formulated into a binder, and it cannot be evenly dispersed in the high-temperature mortar to give full play to its role. Therefore, in the present invention, vinyl triethoxysilane is first used to modify the ceramic fiber, vinyl is introduced, and thiol is further introduced on polyvinyl alcohol, and then the two are grafted together by a click reaction to obtain polyvinyl alcohol modified ceramic fiber. In addition, since polyvinyl alcohol is also often used as a mortar binder, the modification degree of the polyvinyl alcohol modified ceramic fiber is controlled by controlling the amount of raw materials in the scheme, so that the polyvinyl alcohol modified ceramic fiber also has certain bonding properties. Finally, the polyvinyl alcohol modified ceramic fiber prepared by the present invention can be evenly dispersed in the binder, and then evenly dispersed in the high-temperature mortar, which has a significant effect on the thermal properties and bonding properties of the high-temperature mortar. When the high-temperature mortar is not solidified, it can cooperate with silica sol and aluminum dihydrogen phosphate to promote the bonding of mortar powder and enhance the bonding with the masonry; after the high-temperature mortar is solidified, the ceramic fiber can be used as a "skeleton-type" binder to further promote the close bonding of the components, avoid cracking due to temperature changes, and ensure the stability of the furnace structure. The amount of polyvinyl alcohol modified ceramic fiber added should also be controlled within a certain range. If too much is added, the fluidity of the high-temperature mortar will be affected, making the workability of the high-temperature mortar worse, and also increasing the cost.
[0026] Furthermore, the dispersant is obtained by mixing calcium lignin sulfonate and sodium carbonate in a mass ratio of 2:1.
[0027] Furthermore, the water reducing agent includes but is not limited to a combination of one or more of sodium tripolyphosphate, sodium polyphosphate, and ammonium polyacrylate.
[0028] Furthermore, the anti-carburizing agent is composed of silicate and rare earth oxide in a mass ratio of 4:(1-2); the silicate is one or a combination of sodium silicate and potassium silicate; the rare earth oxide is one or a combination of yttrium oxide and cerium oxide.
[0029] Because of the existence of electric potential in the high temperature mortar during the mixing process, the surface adsorption of particles in the high temperature mortar is strong, the fluidity of the high temperature mortar is poor, the viscosity is large, and the construction operability is difficult. Therefore, in the scheme, dispersants and water reducers are added therein, and the two can synergistically improve the dispersibility and hydrophilicity of the high temperature mortar during the mixing process, thereby effectively improving the bonding strength of the high temperature mortar. At the same time, since the high temperature mortar is used in a high temperature environment for a long time, the high carbon gas produced by fuel combustion can easily penetrate into the high temperature mortar, resulting in a decrease in the performance of the high temperature mortar. Therefore, in the present invention, an anti-carburizing agent (silicate, rare earth oxide) is further added, wherein the silicate can form a silicate protective layer at high temperature, which can prevent carbon penetration; and the rare earth oxide itself also has the effect of resisting carbon penetration, and can also make the silicate protective layer more dense, further enhancing the anti-carbon penetration performance of the high temperature mortar. In addition, the protective film also has good high temperature resistance and corrosion resistance, and can well protect the performance and structural stability of the high temperature mortar.
[0030] Furthermore, the preparation method of the high-temperature mortar is as follows: (1) weighing the components of mortar powder, binder, and additive according to the raw material ratio, and then mixing the three components evenly; (2) after the mortar powder and binder are mixed evenly, adding the additive thereto, and mixing the three components evenly to obtain the high-temperature mortar.
[0031] Compared with the prior art, the present invention has the following beneficial effects:
[0032] 1. In the present invention, by simultaneously introducing light mullite brick powder, alumina powder and silicon carbide powder as raw materials of high temperature mortar, the three synergistically obtain high temperature mortar with excellent thermal insulation performance, low thermal expansion coefficient and good thermal shock resistance; and by setting the particle grading, the bonding time and shrinkage rate of the high temperature mortar can be effectively controlled, so that the high temperature mortar has better performance, thereby better ensuring the stability of the furnace structure;
[0033] 2. In the present invention, hydroxypropyl cellulose is used to modify bentonite, thereby enhancing the dispersibility of bentonite in high-temperature mortar, thereby further improving the construction performance, bonding performance, and thermal shock resistance of the high-temperature mortar;
[0034] 3. The present invention modifies the ceramic fiber to enhance its dispersibility, so that it can be evenly dispersed in the high-temperature cement; before the high-temperature cement is cured, it plays a role in promoting adhesion together with silica sol and aluminum dihydrogen phosphate; after curing, it can also be used as a "skeleton-type" binder to avoid cracking caused by factors such as temperature, greatly improving the thermal shock resistance of the high-temperature cement;
[0035] 4. The present invention further adds dispersants and water reducers to improve the dispersibility and hydrophilicity of the high-temperature mortar, thereby improving the bonding properties of the high-temperature mortar; at the same time, an anti-carburizing agent is also added, which can form a dense protective layer on the surface of the high-temperature mortar, which can prevent carbon penetration and has certain corrosion resistance, and has a protective effect on the high-temperature mortar. DETAILED DESCRIPTION
[0036] Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without making any creative work shall fall within the scope of protection of the present invention.
[0037] It should be noted that the purchasers of all raw materials involved in the present invention include, without any special restrictions, illustratively:
[0038] Lightweight mullite brick powder, particle size <0.074mm and particle size 0.074~1mm; alumina powder, particle size <0.074mm and particle size 0.074~1mm; silicon carbide powder, particle size <0.074mm and particle size 0.074~1mm, all purchased from Gongyi Chenyi Refractory Abrasive Co., Ltd.;
[0039] Hydroxypropyl cellulose, purity 99.5%, purchased from Hubei Jusheng Technology Co., Ltd.;
[0040] Sodium bentonite, CAS number: 85049-30-5, product number: PA97816, purchased from Guangdong Wengjiang Chemical Reagent Co., Ltd.;
[0041] Silica sol, CAS number: 14808-60-7, product number: 4163, purchased from Wuhan Jiyesheng Chemical Co., Ltd.;
[0042] Vinyl triethoxysilane, purity 99%; thioglycolic acid, purity 99%; sodium lignin sulfonate, purity 99%; sodium tripolyphosphate, purity 99%; sodium silicate, purity 99%; sodium dihydrogen phosphate, purity 99%, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.;
[0043] Photoinitiator model IHT-PI MBF, CAS number: 15206-55-0, purchased from Hubei Jusheng Technology Co., Ltd.;
[0044] Zirconia fibers, with a diameter of 2 to 4 μm and a length of 20 to 100 μm, were purchased from Foshan Yinai Energy Saving Materials Co., Ltd.
[0045] Polyvinyl alcohol, model: 1795, purity: 99%, CAS number: 9002-89-5, item number: 9002-89-5, purchased from Hubei Qifei Pharmaceutical Chemical Co., Ltd.;
[0046] Yttrium oxide, with a purity of 99.99%, was purchased from Shanghai Jinjinle Industrial Co., Ltd.
[0047] Suzhou clay is obtained from Wuzhong, Suzhou, kaolin, the specific parameters are shown in Table 1:
[0048] Table 1
[0049]
[0050] Guangdong clay is obtained from Qingyuan, Guangdong, kaolin, the specific parameters are shown in Table 2:
[0051] Table 2
[0052]
[0053] Example 1: A method for preparing high temperature cement:
[0054] Step 1: preparing hydroxypropyl cellulose modified sodium bentonite: grinding 6 parts of sodium bentonite through a 1 mm sieve, then slowly adding it to a hydroxypropyl cellulose solution (0.24 parts of hydroxypropyl cellulose are added to 10 parts of deionized water and mixed evenly to prepare), stirring and mixing at a speed of 40 r / min for 8 hours, filtering, drying, grinding, and passing through a 1 mm sieve to obtain hydroxypropyl cellulose modified sodium bentonite;
[0055] Step 2: Preparation of polyvinyl alcohol modified zirconia fiber: (1) Add 0.1 parts of vinyl triethoxysilane, deionized water and anhydrous ethanol in a mass ratio of 1:1:10 into a reaction container, stir and mix, add acetic acid to adjust the pH to 5, continue stirring and mixing for 10 minutes to obtain a silane hydrolyzate; (2) Disperse 2 parts of zirconia fiber in n-butanol to obtain a 5wt% zirconia fiber dispersion; (3) Heat the zirconia fiber dispersion to 80°C, and slowly drop the silane hydrolyzate. After the dropwise addition is complete, continue stirring for 6 h, filtered, washed and dried to obtain vinyl zirconium oxide fiber; (4) added 4 parts of polyvinyl alcohol and 3.6 parts of thioglycolic acid to a 5wt% sulfuric acid solution, stirred and reacted at 80°C for 3h, and purified by dialysis to obtain thiolated polyvinyl alcohol; (5) added 5 parts of thiolated polyvinyl alcohol, 2 parts of vinyl zirconium oxide fiber and 0.1 part of photoinitiator to anhydrous ethanol, ultrasonically dispersed for 10min, irradiated with 365nm ultraviolet light for 30min, separated, washed and dried to obtain polyvinyl alcohol modified zirconia fiber;
[0056] Step 3: (1) Weighing clay powder: 35 parts of graded lightweight mullite brick powder (including 78% lightweight mullite brick powder with a particle size of less than 0.074 mm and 22% lightweight mullite brick powder with a particle size of 0.074-1 mm), 26 parts of graded alumina powder (including 78% alumina powder with a particle size of less than 0.074 mm and 22% alumina powder with a particle size of 0.074-1 mm), 9 parts of graded silicon carbide powder (including 78% silicon carbide powder with a particle size of less than 0.074 mm and 22% silicon carbide powder with a particle size of 0.074-1 mm), 22 parts of Suzhou clay, 15 parts of Guangdong clay, and 4.28 parts of hydroxypropyl cellulose modified sodium bentonite; and mixing the weighed clay powder components evenly;
[0057] (2) Weighing a binder: Mix silica sol, aluminum dihydrogen phosphate, polyvinyl alcohol-modified zirconia fiber, and deionized water in a mass ratio of 2:0.8:0.3:2;
[0058] (3) Weighing additives: 1) Dispersant: calcium lignin sulfonate and sodium carbonate are mixed in a mass ratio of 2:1; 2) Water reducer: sodium tripolyphosphate; 3) Anti-carburizing agent: sodium silicate and yttrium oxide are mixed in a mass ratio of 4:1; 4) The dispersant, water reducer and anti-carburizing agent are mixed uniformly in a mass ratio of 1:3:2;
[0059] (4) Weigh the raw materials according to the mass fraction ratio: 73% of cement powder, 25% of binder, and 2% of additive;
[0060] (5) After the clay powder and the binder are evenly mixed, the additives are added thereto, and the three are evenly mixed to obtain high-temperature clay.
[0061] Example 2: A method for preparing high temperature cement:
[0062] Step 1: Preparation of hydroxypropyl cellulose modified sodium bentonite: 6 parts of sodium bentonite were ground through a 1 mm sieve, and then slowly added to a hydroxypropyl cellulose solution (0.12 parts of hydroxypropyl cellulose were added to 10 parts of deionized water and mixed uniformly), stirred and mixed at a speed of 40 r / min for 8 hours, filtered, dried, ground, and passed through a 1 mm sieve to obtain hydroxypropyl cellulose modified sodium bentonite;
[0063] Step 2: Preparation of polyvinyl alcohol modified zirconia fiber: (1) Add 0.1 parts of vinyl triethoxysilane, deionized water and anhydrous ethanol in a mass ratio of 1:1:10 into a reaction container, stir and mix, add acetic acid to adjust the pH to 5, continue stirring and mixing for 10 minutes to obtain a silane hydrolyzate; (2) Disperse 2 parts of zirconia fiber in n-butanol to obtain a 5wt% zirconia fiber dispersion; (3) Heat the zirconia fiber dispersion to 80°C, and slowly drop the silane hydrolyzate. After the dropwise addition is complete, continue stirring for 6 h, filtered, washed and dried to obtain vinyl zirconium oxide fiber; (4) added 4 parts of polyvinyl alcohol and 3.2 parts of thioglycolic acid to a 5wt% sulfuric acid solution, stirred and reacted at 80°C for 3h, and purified by dialysis to obtain thiolated polyvinyl alcohol; (5) added 4 parts of thiolated polyvinyl alcohol, 2 parts of vinyl zirconium oxide fiber and 0.1 part of photoinitiator to anhydrous ethanol, ultrasonically dispersed for 10min, irradiated with 365nm ultraviolet light for 30min, separated, washed and dried to obtain polyvinyl alcohol modified zirconia fiber;
[0064] Step 3: (1) Weighing clay powder: 35 parts of graded lightweight mullite brick powder (including 78% lightweight mullite brick powder with a particle size of less than 0.074 mm and 22% lightweight mullite brick powder with a particle size of 0.074-1 mm), 26 parts of graded alumina powder (including 78% alumina powder with a particle size of less than 0.074 mm and 22% alumina powder with a particle size of 0.074-1 mm), 9 parts of graded silicon carbide powder (including 78% silicon carbide powder with a particle size of less than 0.074 mm and 22% silicon carbide powder with a particle size of 0.074-1 mm), 22 parts of Suzhou clay, 15 parts of Guangdong clay, and 2.14 parts of hydroxypropyl cellulose modified sodium bentonite; and mixing the weighed clay powder components uniformly;
[0065] (2) Weighing a binder: uniformly mixing silica sol, aluminum dihydrogen phosphate, polyvinyl alcohol-modified zirconia fiber, and deionized water in a mass ratio of 2:0.8:0.2:2;
[0066] (3) Weighing additives: 1) Dispersant: calcium lignin sulfonate and sodium carbonate are mixed in a mass ratio of 2:1; 2) Water reducer: sodium tripolyphosphate; 3) Anti-carburizing agent: sodium silicate and yttrium oxide are mixed in a mass ratio of 4:1; 4) The dispersant, water reducer and anti-carburizing agent are mixed uniformly in a mass ratio of 1:3:2;
[0067] (4) Weigh the raw materials according to the mass fraction ratio: 73% of cement powder, 25% of binder, and 2% of additive;
[0068] (5) After the clay powder and the binder are evenly mixed, the additives are added thereto, and the three are evenly mixed to obtain high-temperature clay.
[0069] Example 3: A method for preparing high temperature cement:
[0070] Step 1: preparing hydroxypropyl cellulose modified sodium bentonite: grinding 6 parts of sodium bentonite through a 1 mm sieve, then slowly adding it to a hydroxypropyl cellulose solution (0.3 parts of hydroxypropyl cellulose is added to 10 parts of deionized water and mixed evenly to prepare), stirring and mixing at a speed of 40 r / min for 8 hours, filtering, drying, grinding, and passing through a 1 mm sieve to obtain hydroxypropyl cellulose modified sodium bentonite;
[0071] Step 2: Preparation of polyvinyl alcohol modified zirconia fiber: (1) Add 0.12 parts of vinyl triethoxysilane, deionized water and anhydrous ethanol in a mass ratio of 1:1:10 into a reaction container, stir and mix, add acetic acid to adjust the pH to 5, continue stirring and mixing for 10 minutes to obtain a silane hydrolyzate; (2) Disperse 2 parts of zirconia fiber in n-butanol to obtain a 5wt% zirconia fiber dispersion; (3) Heat the zirconia fiber dispersion to 80°C, and slowly drop the silane hydrolyzate. After the dropwise addition is complete, continue stirring for 6 h, filtered, washed and dried to obtain vinyl zirconium oxide fiber; (4) added 4 parts of polyvinyl alcohol and 4 parts of thioglycolic acid to a 5wt% sulfuric acid solution, stirred and reacted at 80°C for 3h, and purified by dialysis to obtain thiolated polyvinyl alcohol; (5) added 6.67 parts of thiolated polyvinyl alcohol, 2 parts of vinyl zirconium oxide fiber and 0.1 part of photoinitiator to anhydrous ethanol, ultrasonically dispersed for 10min, irradiated with 365nm ultraviolet light for 30min, separated, washed and dried to obtain polyvinyl alcohol modified zirconia fiber;
[0072] Step 3: (1) Weighing clay powder: 35 parts of graded lightweight mullite brick powder (including 78% lightweight mullite brick powder with a particle size of less than 0.074 mm and 22% lightweight mullite brick powder with a particle size of 0.074-1 mm), 26 parts of graded alumina powder (including 78% alumina powder with a particle size of less than 0.074 mm and 22% alumina powder with a particle size of 0.074-1 mm), 9 parts of graded silicon carbide powder (including 78% silicon carbide powder with a particle size of less than 0.074 mm and 22% silicon carbide powder with a particle size of 0.074-1 mm), 22 parts of Suzhou clay, 15 parts of Guangdong clay, and 5.35 parts of hydroxypropyl cellulose modified sodium bentonite; and mixing the weighed clay powder components evenly;
[0073] (2) Weighing a binder: Mix silica sol, aluminum dihydrogen phosphate, polyvinyl alcohol-modified zirconia fiber, and deionized water in a mass ratio of 2:0.8:0.4:2;
[0074] (3) Weighing additives: 1) Dispersant: calcium lignin sulfonate and sodium carbonate are mixed in a mass ratio of 2:1; 2) Water reducer: sodium tripolyphosphate; 3) Anti-carburizing agent: sodium silicate and yttrium oxide are mixed in a mass ratio of 4:1; 4) The dispersant, water reducer and anti-carburizing agent are mixed uniformly in a mass ratio of 1:3:2;
[0075] (4) Weigh the raw materials according to the mass fraction ratio: 73% of cement powder, 25% of binder, and 2% of additive;
[0076] (5) After the clay powder and the binder are evenly mixed, the additives are added thereto, and the three are evenly mixed to obtain high-temperature clay.
[0077] Based on Example 1, a control experiment is carried out, and comparative examples 1 to 5 are set as follows:
[0078] Comparative Example 1: Comparative Example 1 is based on Example 1, with the following adjustments: silicon carbide powder is not added to the cement powder, and other processes remain unchanged;
[0079] A method for preparing high temperature cement:
[0080] Step 1: preparing hydroxypropyl cellulose modified sodium bentonite: grinding 6 parts of sodium bentonite through a 1 mm sieve, then slowly adding it to a hydroxypropyl cellulose solution (0.24 parts of hydroxypropyl cellulose are added to 10 parts of deionized water and mixed evenly to prepare), stirring and mixing at a speed of 40 r / min for 8 hours, filtering, drying, grinding, and passing through a 1 mm sieve to obtain hydroxypropyl cellulose modified sodium bentonite;
[0081] Step 2: Preparation of polyvinyl alcohol modified zirconia fiber: (1) Add 0.1 parts of vinyl triethoxysilane, deionized water and anhydrous ethanol in a mass ratio of 1:1:10 into a reaction container, stir and mix, add acetic acid to adjust the pH to 5, continue stirring and mixing for 10 minutes to obtain a silane hydrolyzate; (2) Disperse 2 parts of zirconia fiber in n-butanol to obtain a 5wt% zirconia fiber dispersion; (3) Heat the zirconia fiber dispersion to 80°C, and slowly drop the silane hydrolyzate. After the dropwise addition is complete, continue stirring for 6 h, filtered, washed and dried to obtain vinyl zirconium oxide fiber; (4) added 4 parts of polyvinyl alcohol and 3.6 parts of thioglycolic acid to a 5wt% sulfuric acid solution, stirred and reacted at 80°C for 3h, and purified by dialysis to obtain thiolated polyvinyl alcohol; (5) added 5 parts of thiolated polyvinyl alcohol, 2 parts of vinyl zirconium oxide fiber and 0.1 part of photoinitiator to anhydrous ethanol, ultrasonically dispersed for 10min, irradiated with 365nm ultraviolet light for 30min, separated, washed and dried to obtain polyvinyl alcohol modified zirconia fiber;
[0082] Step 3: (1) Weighing the following cement powders: 35 parts of graded lightweight mullite brick powder (including 78% lightweight mullite brick powder with a particle size of less than 0.074 mm and 22% lightweight mullite brick powder with a particle size of 0.074-1 mm), 26 parts of graded alumina powder (including 78% alumina powder with a particle size of less than 0.074 mm and 22% alumina powder with a particle size of 0.074-1 mm), 22 parts of Suzhou mud, 15 parts of Guangdong mud, and 3.92 parts of hydroxypropyl cellulose modified sodium bentonite; and mixing the weighed cement powder components uniformly;
[0083] (2) Weighing a binder: Mix silica sol, aluminum dihydrogen phosphate, polyvinyl alcohol-modified zirconia fiber, and deionized water in a mass ratio of 2:0.8:0.3:2;
[0084] (3) Weighing additives: 1) Dispersant: calcium lignin sulfonate and sodium carbonate are mixed in a mass ratio of 2:1; 2) Water reducer: sodium tripolyphosphate; 3) Anti-carburizing agent: sodium silicate and yttrium oxide are mixed in a mass ratio of 4:1; 4) The dispersant, water reducer and anti-carburizing agent are mixed uniformly in a mass ratio of 1:3:2;
[0085] (4) Weigh the raw materials according to the mass fraction ratio: 73% of cement powder, 25% of binder, and 2% of additive;
[0086] (5) After the clay powder and the binder are evenly mixed, the additives are added thereto, and the three are evenly mixed to obtain high-temperature clay.
[0087] Comparative Example 2: Comparative Example 2 is based on Example 1, with the following adjustments: sodium bentonite is not modified, and other processes remain unchanged;
[0088] A method for preparing high temperature cement:
[0089] Step 1: Preparation of polyvinyl alcohol modified zirconia fiber: (1) Add 0.1 parts of vinyl triethoxysilane, deionized water and anhydrous ethanol in a mass ratio of 1:1:10 into a reaction container, stir and mix, add acetic acid to adjust the pH to 5, continue stirring and mixing for 10 minutes to obtain a silane hydrolyzate; (2) Disperse 2 parts of zirconia fiber in n-butanol to obtain a 5wt% zirconia fiber dispersion; (3) Heat the zirconia fiber dispersion to 80°C, and slowly drop the silane hydrolyzate. After the dropwise addition is complete, continue stirring for 6 h, filtered, washed and dried to obtain vinyl zirconium oxide fiber; (4) added 4 parts of polyvinyl alcohol and 3.6 parts of thioglycolic acid to a 5wt% sulfuric acid solution, stirred and reacted at 80°C for 3h, and purified by dialysis to obtain thiolated polyvinyl alcohol; (5) added 5 parts of thiolated polyvinyl alcohol, 2 parts of vinyl zirconium oxide fiber and 0.1 part of photoinitiator to anhydrous ethanol, ultrasonically dispersed for 10min, irradiated with 365nm ultraviolet light for 30min, separated, washed and dried to obtain polyvinyl alcohol modified zirconia fiber;
[0090] Step 2: (1) Weighing clay powder: 35 parts of graded lightweight mullite brick powder (including 78% lightweight mullite brick powder with a particle size of less than 0.074 mm and 22% lightweight mullite brick powder with a particle size of 0.074-1 mm), 26 parts of graded alumina powder (including 78% alumina powder with a particle size of less than 0.074 mm and 22% alumina powder with a particle size of 0.074-1 mm), 9 parts of graded silicon carbide powder (including 78% silicon carbide powder with a particle size of less than 0.074 mm and 22% silicon carbide powder with a particle size of 0.074-1 mm), 22 parts of Suzhou clay, 15 parts of Guangdong clay, and 4.28 parts of sodium bentonite; and mixing the weighed clay powder components uniformly;
[0091] (2) Weighing a binder: Mix silica sol, aluminum dihydrogen phosphate, polyvinyl alcohol-modified zirconia fiber, and deionized water in a mass ratio of 2:0.8:0.3:2;
[0092] (3) Weighing additives: 1) Dispersant: calcium lignin sulfonate and sodium carbonate are mixed in a mass ratio of 2:1; 2) Water reducer: sodium tripolyphosphate; 3) Anti-carburizing agent: sodium silicate and yttrium oxide are mixed in a mass ratio of 4:1; 4) The dispersant, water reducer and anti-carburizing agent are mixed uniformly in a mass ratio of 1:3:2;
[0093] (4) Weigh the raw materials according to the mass fraction ratio: 73% of cement powder, 25% of binder, and 2% of additive;
[0094] (5) After the clay powder and the binder are evenly mixed, the additives are added thereto, and the three are evenly mixed to obtain high-temperature clay.
[0095] Comparative Example 3: Comparative Example 3 is based on Example 1, with the following adjustments: no polyvinyl alcohol-modified zirconia fiber is added to the binder, and other processes remain unchanged;
[0096] A method for preparing high temperature cement:
[0097] Step 1: preparing hydroxypropyl cellulose modified sodium bentonite: grinding 6 parts of sodium bentonite through a 1 mm sieve, then slowly adding it to a hydroxypropyl cellulose solution (0.24 parts of hydroxypropyl cellulose are added to 10 parts of deionized water and mixed evenly to prepare), stirring and mixing at a speed of 40 r / min for 8 hours, filtering, drying, grinding, and passing through a 1 mm sieve to obtain hydroxypropyl cellulose modified sodium bentonite;
[0098] Step 2: (1) Weighing clay powder: 35 parts of graded lightweight mullite brick powder (including 78% lightweight mullite brick powder with a particle size of less than 0.074 mm and 22% lightweight mullite brick powder with a particle size of 0.074-1 mm), 26 parts of graded alumina powder (including 78% alumina powder with a particle size of less than 0.074 mm and 22% alumina powder with a particle size of 0.074-1 mm), 9 parts of graded silicon carbide powder (including 78% silicon carbide powder with a particle size of less than 0.074 mm and 22% silicon carbide powder with a particle size of 0.074-1 mm), 22 parts of Suzhou clay, 15 parts of Guangdong clay, and 4.28 parts of hydroxypropyl cellulose modified sodium bentonite; and mixing the weighed clay powder components uniformly;
[0099] (2) Weighing the binder: Mix silica sol, aluminum dihydrogen phosphate, and deionized water in a mass ratio of 2:0.8:2;
[0100] (3) Weighing additives: 1) Dispersant: calcium lignin sulfonate and sodium carbonate are mixed in a mass ratio of 2:1; 2) Water reducer: sodium tripolyphosphate; 3) Anti-carburizing agent: sodium silicate and yttrium oxide are mixed in a mass ratio of 4:1; 4) The dispersant, water reducer and anti-carburizing agent are mixed uniformly in a mass ratio of 1:3:2;
[0101] (4) Weigh the raw materials according to the mass fraction ratio: 73% of cement powder, 25% of binder, and 2% of additive;
[0102] (5) After the clay powder and the binder are evenly mixed, the additives are added thereto, and the three are evenly mixed to obtain high-temperature clay.
[0103] Comparative Example 4: Comparative Example 4 is based on Example 1, with the following adjustments: the zirconia fiber is not modified, and other processes remain unchanged;
[0104] A method for preparing high temperature cement:
[0105] Step 1: preparing hydroxypropyl cellulose modified sodium bentonite: grinding 6 parts of sodium bentonite through a 1 mm sieve, then slowly adding it to a hydroxypropyl cellulose solution (0.24 parts of hydroxypropyl cellulose are added to 10 parts of deionized water and mixed evenly to prepare), stirring and mixing at a speed of 40 r / min for 8 hours, filtering, drying, grinding, and passing through a 1 mm sieve to obtain hydroxypropyl cellulose modified sodium bentonite;
[0106] Step 2: (1) Weighing clay powder: 35 parts of graded lightweight mullite brick powder (including 78% lightweight mullite brick powder with a particle size of less than 0.074 mm and 22% lightweight mullite brick powder with a particle size of 0.074-1 mm), 26 parts of graded alumina powder (including 78% alumina powder with a particle size of less than 0.074 mm and 22% alumina powder with a particle size of 0.074-1 mm), 9 parts of graded silicon carbide powder (including 78% silicon carbide powder with a particle size of less than 0.074 mm and 22% silicon carbide powder with a particle size of 0.074-1 mm), 22 parts of Suzhou clay, 15 parts of Guangdong clay, and 4.28 parts of hydroxypropyl cellulose modified sodium bentonite; and mixing the weighed clay powder components uniformly;
[0107] (2) Weighing the binder: Mix silica sol, aluminum dihydrogen phosphate, zirconium oxide fiber, and deionized water in a mass ratio of 2:0.8:0.3:2;
[0108] (3) Weighing additives: 1) Dispersant: calcium lignin sulfonate and sodium carbonate are mixed in a mass ratio of 2:1; 2) Water reducer: sodium tripolyphosphate; 3) Anti-carburizing agent: sodium silicate and yttrium oxide are mixed in a mass ratio of 4:1; 4) The dispersant, water reducer and anti-carburizing agent are mixed uniformly in a mass ratio of 1:3:2;
[0109] (4) Weigh the raw materials according to the mass fraction ratio: 73% of cement powder, 25% of binder, and 2% of additive;
[0110] (5) After the clay powder and the binder are evenly mixed, the additives are added thereto, and the three are evenly mixed to obtain high-temperature clay.
[0111] Comparative Example 5: Comparative Example 5 is based on Example 1, with the following adjustments: no anti-carburizing agent is added to the additive, and other processes remain unchanged;
[0112] A method for preparing high temperature cement:
[0113] Step 1: preparing hydroxypropyl cellulose modified sodium bentonite: grinding 6 parts of sodium bentonite through a 1 mm sieve, then slowly adding it to a hydroxypropyl cellulose solution (0.24 parts of hydroxypropyl cellulose are added to 10 parts of deionized water and mixed evenly to prepare), stirring and mixing at a speed of 40 r / min for 8 hours, filtering, drying, grinding, and passing through a 1 mm sieve to obtain hydroxypropyl cellulose modified sodium bentonite;
[0114] Step 2: Preparation of polyvinyl alcohol modified zirconia fiber: (1) Add 0.1 parts of vinyl triethoxysilane, deionized water and anhydrous ethanol in a mass ratio of 1:1:10 into a reaction container, stir and mix, add acetic acid to adjust the pH to 5, continue stirring and mixing for 10 minutes to obtain a silane hydrolyzate; (2) Disperse 2 parts of zirconia fiber in n-butanol to obtain a 5wt% zirconia fiber dispersion; (3) Heat the zirconia fiber dispersion to 80°C, and slowly drop the silane hydrolyzate. After the dropwise addition is complete, continue stirring for 6 h, and then filtered, washed and dried to obtain vinyl zirconium oxide fiber; (4) adding 4 parts of polyvinyl alcohol and 3.6 parts of thioglycolic acid to a 5wt% sulfuric acid solution, stirring and reacting at 80°C for 3h, and purifying by dialysis to obtain thiolated polyvinyl alcohol; (5) adding 5 parts of thiolated polyvinyl alcohol, 2 parts of vinyl zirconium oxide fiber and 0.1 part of photoinitiator to anhydrous ethanol, ultrasonically dispersing for 10min, irradiating with 365nm ultraviolet light for 30min, separating, washing and drying to obtain polyvinyl alcohol modified zirconia fiber.
[0115] Step 3: (1) Weighing clay powder: 35 parts of graded lightweight mullite brick powder (including 78% lightweight mullite brick powder with a particle size of less than 0.074 mm and 22% lightweight mullite brick powder with a particle size of 0.074-1 mm), 26 parts of graded alumina powder (including 78% alumina powder with a particle size of less than 0.074 mm and 22% alumina powder with a particle size of 0.074-1 mm), 9 parts of graded silicon carbide powder (including 78% silicon carbide powder with a particle size of less than 0.074 mm and 22% silicon carbide powder with a particle size of 0.074-1 mm), 22 parts of Suzhou clay, 15 parts of Guangdong clay, and 4.28 parts of hydroxypropyl cellulose modified sodium bentonite; and mixing the weighed clay powder components evenly;
[0116] (2) Weighing a binder: mixing silica sol, aluminum dihydrogen phosphate, polyvinyl alcohol-modified ceramic fiber, and deionized water in a mass ratio of 2:0.8:0.3:2;
[0117] (3) Weighing additives: 1) Dispersant: calcium lignin sulfonate and sodium carbonate mixed in a mass ratio of 2:1; 2) Water reducer: sodium tripolyphosphate; 3) Mix the dispersant and water reducer in a mass ratio of 1:3;
[0118] (4) Weigh the raw materials according to the mass fraction ratio: 73% of cement powder, 25% of binder, and 2% of additive;
[0119] (5) After the clay powder and the binder are evenly mixed, the additives are added thereto, and the three are evenly mixed to obtain high-temperature clay.
[0120] Performance test: The high temperature cement prepared in Examples 1 to 3 and Comparative Examples 1 to 5 was subjected to relevant performance tests, as follows:
[0121] (1) According to GB / T 22459.7-2008 and GB / T 7320-2018, a linear expansion test was performed and heated to 1500°C;
[0122] (2) According to the standard of GB / T 22459.4-2022, the flexural viscosity test was carried out at 1500°C for 3 h.
[0123] The test results of the above test contents are shown in Table 3 below:
[0124] Table 3
[0125]
[0126]
[0127] Analysis of results: From the data in Table 3 above, it can be seen that the linear expansion rate of the high-temperature mortar prepared by the present invention when heated to 1500°C is as low as 0.1%; the flexural viscosity after being kept at 1500°C for 3 hours is as high as 10.3MPa; this shows that the high-temperature mortar prepared by the present invention has excellent overall performance and bonding properties, and will not show obvious volume changes and performance degradation after heating, and the product quality is excellent.
[0128] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A high temperature mortar, characterized in that: The composition comprises the following components by mass fraction: 70-75% of cement powder, 24-27% of binder, and 1-3% of additive; The cement powder comprises the following components in parts by weight: 25-40 parts of graded lightweight mullite brick powder, 15-30 parts of graded alumina powder, 8-10 parts of graded silicon carbide powder, 15-25 parts of Suzhou mud, 10-20 parts of Guangdong mud, and 1.46-6.25 parts of hydroxypropyl cellulose modified bentonite; The binder is obtained by mixing silica sol, aluminum dihydrogen phosphate, polyvinyl alcohol modified ceramic fiber and deionized water in a mass ratio of 2: (0.5-1): (0.2-0.4): 2; The additive is obtained by mixing a dispersant, a water reducing agent and an anti-carburizing agent in a mass ratio of 1:3:
2.
2. The high temperature mortar according to claim 1, characterized in that: The specific grading ratio of the graded lightweight mullite brick powder is: 75-80% of lightweight mullite brick powder with a particle size of less than 0.074mm, and 20-25% of lightweight mullite brick powder with a particle size of 0.074-1mm; the specific grading ratio of the graded alumina powder is: 75-80% of alumina powder with a particle size of less than 0.074mm, and 20-25% of alumina powder with a particle size of 0.074-1mm; the specific grading ratio of the graded silicon carbide powder is: 75-80% of silicon carbide powder with a particle size of less than 0.074mm, and 20-25% of silicon carbide powder with a particle size of 0.074-1mm.
3. The high temperature mortar according to claim 1, characterized in that: The particle size of the Suzhou mud and Guangdong mud is 3 to 5 μm.
4. The high temperature mortar according to claim 1, characterized in that: The preparation method of the hydroxypropyl cellulose modified bentonite is as follows: grinding the bentonite through a 1 mm sieve, then slowly adding the bentonite into a hydroxypropyl cellulose solution, stirring and mixing at a speed of 30 to 50 r / min for 5 to 10 hours, filtering, drying, grinding, and passing through a 1 mm sieve to obtain the hydroxypropyl cellulose modified bentonite.
5. The high temperature mortar according to claim 4, characterized in that: The bentonite is any one of sodium-based bentonite and calcium-based bentonite; the mass ratio of the bentonite to hydroxypropyl cellulose is 1:(0.02-0.05).
6. The high temperature mortar according to claim 1, characterized in that: The preparation method of the polyvinyl alcohol modified ceramic fiber is as follows: (1) adding vinyl triethoxysilane, deionized water and anhydrous ethanol in a mass ratio of 1:1:10 into a reaction container, stirring and mixing, and adding acetic acid to adjust the pH to 4.5-5.5, and continuing to stir and mix for 5-15 minutes to obtain a silane hydrolyzate; (2) dispersing the ceramic fiber in n-butanol to obtain a 5wt% ceramic fiber dispersion; (3) heating the ceramic fiber dispersion to 70-90°C, and slowly dropping the silane hydrolyzate until the dropping is complete. After that, stirring is continued for 2 to 8 hours, and vinyl ceramic fibers are obtained by filtering, washing, and drying; (4) polyvinyl alcohol and thioglycolic acid are added to a 4 to 6 wt % sulfuric acid solution, and the mixture is stirred and reacted at 70 to 90° C. for 1 to 4 hours, and purified by dialysis to obtain thiolated polyvinyl alcohol; (5) thiolated polyvinyl alcohol, vinyl ceramic fibers, and a photoinitiator are added to anhydrous ethanol, and ultrasonically dispersed for 5 to 15 minutes, and reacted by ultraviolet irradiation for 15 to 45 minutes, and separated, washed, and dried to obtain polyvinyl alcohol-modified ceramic fibers.
7. The high temperature mortar according to claim 1, characterized in that: The mass ratio of the vinyl triethoxysilane and the ceramic fiber is (0.04-0.06):1; the mass ratio of the polyvinyl alcohol and the thioglycolic acid is 1:(0.8-1); the mass ratio of the thiolated polyvinyl alcohol, the vinylized ceramic fiber and the photoinitiator is 1:(0.3-0.5):(0.01-0.03); the ceramic fiber includes a combination of one or more of zirconium oxide fiber, silicon carbide fiber, silicon nitride fiber, aluminum silicate fiber and mullite fiber.
8. The high temperature mortar according to claim 1, characterized in that: The dispersant is obtained by mixing calcium lignin sulfonate and sodium carbonate in a mass ratio of 2:1; the water reducer includes a combination of one or more of sodium tripolyphosphate, sodium polyphosphate, and ammonium polyacrylate; and the anti-carburizing agent is obtained by mixing silicate and rare earth oxide in a mass ratio of 4:(1-2).
9. The high temperature mortar according to claim 8, characterized in that: The silicate is one of sodium silicate and potassium silicate or a combination of both; the rare earth oxide is one of yttrium oxide and cerium oxide or a combination of both.
10. A method for preparing high temperature mortar according to any one of claims 1 to 9, characterized in that: (1) Weigh the components of the mortar powder, binder, and additive according to the raw material ratio, and then mix the three components evenly; (2) After the mortar powder and binder are mixed evenly, add the additive thereto, and wait until the three components are mixed evenly to obtain high-temperature mortar.
Citation Information
Patent Citations
Preparation method for anti-freeze and fire-resistant mortar
CN102746008A
Medium-temperature gunning mix
CN103755371A
High-temperature-resistant cement and preparation method for same
CN105541356A
Refractory mortar and preparation method thereof
CN109437939A
Surface treatment method of super-hydrophobic multifunctional cellulose-based material
CN110774394A